Are Bacterial Volatile Compounds Poisonous Odors to a Fungal Pathogen Botrytis cinerea, Alarm Signals to Arabidopsis Seedlings for Eliciting Induced Resistance, or Both? - Sharifi, Rouhallah; Ryu, Choong-Min (Frontiers in Microbiology, 2016)
Biological control (biocontrol) agents act on plants via numerous mechanisms, and can be used to protect plants from pathogens. Biocontrol agents can act directly as pathogen antagonists or competitors or indirectly to promote plant induced systemic resistance (ISR). Whether a biocontrol agent acts directly or indirectly depends on the specific strain and the pathosystem type. We reported previously that bacterial volatile organic compounds (VOCs) are determinants for eliciting plant ISR. Emerging data suggest that bacterial VOCs also can directly inhibit fungal and plant growth. The aim of the current study was to differentiate direct and indirect mechanisms of bacterial VOC effects against Botrytis cinerea infection of Arabidopsis. Volatile emissions from Bacillus subtilis GB03 successfully protected Arabidopsis seedlings against B. cinerea. First, we investigated the direct effects of bacterial VOCs on symptom development and different phenological stages of B. cinerea including spore germination, mycelial attachment to the leaf surface, mycelial growth, and sporulation in vitro and in planta. Volatile emissions inhibited hyphal growth in a dose-dependent manner in vitro, and interfered with fungal attachment on the hydrophobic leaf surface. Second, the optimized bacterial concentration that did not directly inhibit fungal growth successfully protected Arabidopsis from fungal infection, which indicates that bacterial VOC-elicited plant ISR has a more important role in biocontrol than direct inhibition of fungal growth on Arabidopsis. We performed qRT-PCR to investigate the priming of the defense-related genes PR1, PDF1.2, and ChiB at 0, 12, 24, and 36 hours post-infection and 14 days after the start of plant exposure to bacterial VOCs. The results indicate that bacterial VOCs potentiate expression of PR1 and PDF1.2 but not ChiB, which stimulates SA- and JA-dependent signaling pathways in plant ISR and protects plants against pathogen colonization. This study provides new evidence for bacterial VOC-elicited plant ISR that protects Arabidopsis plants from infection by the necrotrophic fungus B. cinerea. Our work reveals that bacterial VOCs primarily act via an indirect mechanism to elicit plant ISR, and have a major role in biocontrol against fungal pathogens.